2021
DOI: 10.48083/ozul6913
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Retrograde Ureteral Stenting Failure as an Initial Drainage Method for Emergent Complicated Acute Calculus Obstructive Uropathy

Abstract: Objective: To define predictors for initial retrograde ureteral stenting (RUS) failure with the need for the percutaneous nephrostomy (PCN) insertion as a drainage method in patients with complicated acute calculus obstructive uropathy. Methods: We undertook a retrospective evaluation of patients who presented with complicated obstructive calculus uropathy (acute renal failure or obstructive pyelonephritis) between January 2016 and January 2020. Patients in whom there was failure to visualize ipsilateral urete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Percutaneous nephrostomy insertion and retrograde ureteric stenting have shown to have comparable success rates in obstructive uropathy secondary to urolithiasis; however, radiation exposure, length of stay in the hospital, and associated costs were higher in those with percutaneous nephrostomies when compared to ureteric stenting [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Percutaneous nephrostomy insertion and retrograde ureteric stenting have shown to have comparable success rates in obstructive uropathy secondary to urolithiasis; however, radiation exposure, length of stay in the hospital, and associated costs were higher in those with percutaneous nephrostomies when compared to ureteric stenting [7].…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of a percutaneous nephrostomy or a ureteric stent is sometimes unavoidable in obstructive uropathy [7]. We present two cases of individuals who presented to a district general hospital within the National Health Service (NHS) in the United Kingdom, were treated for urosepsis secondary to an obstructing calculus, and were managed via the use of both antibiotics and the placement of a ureteric stent, done under local anesthesia at the bedside, for source control of the septic patient.…”
Section: Introductionmentioning
confidence: 99%
“…UWT recently was proposed to predict failure of SWL, retrograde ureteral stent placement in addition to failure to manipulate stones during URS [ 12 , 13 , 17 , 18 ]. Increased UWT indicate the presence of impacted ureteral stones.…”
Section: Discussionmentioning
confidence: 99%
“…Increased UWT indicate the presence of impacted ureteral stones. Stone impaction occurred due to ureteral local inflammation, polyps and edema when stone fragments remain at the same location for a prolonged time period [ 18 ]. Yoshida et al, reported that measuring UWT by NCCT before starting treatment can be a good indicative marker for stone passage < 10 mm during MET [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Третє визначення, яке цитується в літературі, -це відсутність візуалізації контрастного середовища поза каменем, а на практиці це визначається інтраопераційно, коли не вдається провести провідник поза конкремент та/або якщо переміщення конкременту не відбувається внаслідок його фіксації до слизової оболонки стінки сечоводу («ускладнений» конкремент) [8].…”
unclassified